Knowledge, Attitude, and Practice (KAP) of Voluntary Blood Donation among Nurses in Mosul Teaching Hospital - Mahmoud Mohammed Ahmed; Ahmed Ali Hussein; Nasir Mufaq Youns (College of Nursing,University of Mosul, 2017)
Background and aim : blood can save millions of lives. The requirement of blood and blood products in a country depends on the population, health care structure, prevalence of conditions requiring regular transfusions, such as hemophilia and thalassemia etc., availability of surgical centers using modern sophisticated techniques, and awareness amongst clinicians regarding the judicious use of blood. The study aimed to assess of Knowledge, Attitude, and Practice (KAP) of Voluntary Blood Donation among nurses at the Mosul Teaching Hospital. Materials and Method: Cross-sectional design was applied in this study that aimed to assessment of knowledge, Attitude, and practice of voluntary blood donation among nurses in Mosul Teaching Hospital. Random sample consists of (152) nurses (99 )Male , ( 53) Female , and the sample age range (median age) 18-60 (26.3±) years. Data were collected from first December 2013 extended from First February 2014.Data were collected from all Mosul Teaching Hospital (Ibn-Sena Teaching Hospital, AL-ZahraweeTeahing Hospital, AL-Salm Teaching Hospital,Ibn-AtherTeahing Hospital and Al-KhansaTeahing Hospital). An interview technique, method was used for data collection and data were analyzed as Frequency, percentage and Chi-Squire. Results: The results of the study show that the Knowledge, Attitude, and Practice(KAP) of Voluntary Blood Donation among nurses in Mosul Teaching Hospital is good knowledge toward blood donation (81.4%), positive attitude about (78.2%),but there were practices of blood donation correct (56.7%) Conclusion: The study concluded that the Nurses in hospitals have good knowledge of voluntary donation and a positive attitude towards donation, but there were disparities in their practices of blood donation. Recommendation: The study recommended there is an urgent need to create and strengthen programs for motivation, recruitment and retention of voluntary blood Donors in our country. Keywords:-Knowledge, Attitude , Practice, Nurses , Voluntary blood donation.